THE IMPACT OF USING FUNCTIONAL STRENGTH TRAINING TO DEVELOP AND ENHANCE THE PERFORMANCE OF WRESTLING GRIPS - T. Ahmed Farooq Tawfeeq Ezzi; Prof. Ferouz Aziz (Galaxy International Interdisciplinary Research Journal, 2024)
This study aims to prepare functional strength training exercises that are appropriate for the research sample in order to improve and develop standing grip performance for freestyle wrestlers, as well as to determine the effects of using these exercises on the research sample individuals in order to improve and develop standing grip performance. Because the selection of the sample is one of the key components of the experimental method and a crucial phase in the research process, the researchers employed the proper approach to address the research topic. Undoubtedly, the researchers consider the research sample from the outset when defining the nature of the issue and the objectives of the investigation. Consequently, a sample of wrestlers from the advanced category—a total of twenty-two wrestlers—were used for the research. They trained in the Al-Adhamiya Club’s wrestling hall. The wrestlers, who are members of Al-Adhamiya Sports Club, were chosen on purpose. As a result, there were twenty wrestlers in the experimental sample, or 90.9% of the research population. Anthropometric measures were used by the researchers to confirm the sample’s homogeneity. The findings demonstrated that, in the post-test grip performance tests, there were significant differences between the experimental and control groups for the functional strength training activities, with the experimental group doing better. Regarding the recommendations, they state that when training wrestlers’ grip performance, functional strength training activities should be used. Additionally, these exercises should replicate skill performance, which includes training the muscles involved in the wrestling grip.